LinkedIn como herramienta para el desarrollo del Orientador Profesional.: LinkedIn as a tool for the development of Vocational counselor - Pilar Martínez Clares, Mirian Martínez Juárez, Javier Pérez Cusó (Revista de Orientación Educacional, 2019)
Entre la nueva generación de páginas web se encuentra LinkedIn, que puede facilitar el desempeño laboral y desarrollo profesional de los orientadores profesionales. Desde este trabajo, a través de un método mixto, se analizan 84 grupos de esta red relacionados con la orientación profesional. Los resultados permiten comprobar que existe una gran heterogeneidad entre los grupos y las temáticas abordadas, que responden a necesidades sociales emergentes. LinkedIn es un buen recurso para crear comunidades virtuales de trabajo, contribuyendo al desarrollo profesional de los orientadores; no obstante, se aprecia un uso focalizado en el intercambio de información, lo que hace necesario una mayor formación en este tipo de recursos para aprovechar todas sus potencialidades. Abstract: Among the new generation of web pages is LinkedIn, it could be employed as a tool that facilitate the work performance of vocational counselor as well as their development. Therefore, from this paper, and with a mixed methodology, 84 groups of this social network related to vocational counselor are analyzed. The results allow verifying that there is heterogeneity between groups and the issues under discussion, but respond to emerging social needs. LinkedIn is a great resource to create real work and learning virtual communities and contributes to professional growth of vocational counselor. Although it is visible a use focused on information exchange, consequently, is necessary awareness and further training in this type of resources in order to seize the opportunities.